The Effect Of Burnout and Psychological Well-Being on Turnover Intentions of Generation Z in the Klaten Region - Nailah Khomsa Fatiha Rizky (Utan Kayu Publishing, 2025)
This study examined the effect of burnout and psychological well-being on turnover intention among 98 Generation Z workers in Klaten Regency. Data were obtained through a survey using a 5-point Likert scale with a total of 30 statement items. All items have been tested for validity and reliability, with a Cronbach's Alpha value of 0.868 for burnout, 0.888 for psychological well-being, and 0.910 for turnover intention, thus the instrument can be declared reliable. Descriptive statistics show that burnout is at a moderate level (M = 28.94; SD = 5.81), psychological well-being is in the good category (M = 32.67; SD = 6.14), and turnover intention is in the moderate category (M = 27.88; SD = 6.02). The results of the regression analysis showed that burnout has a positive and significant effect on turnover intention (? = 0.41; p 0.001). This means that the higher the burnout, the more likely the respondent is to intend to leave their job. In contrast, psychological well-being had a negative and significant effect (? = -0.28; p = 0.001), meaning that a good psychological condition can reduce the tendency to leave work. Regression analysis showed that the model only explained about 46.3% of the variation in turnover intention (R² = 0.463). However, the model was still statistically significant, as indicated by the F-statistic of 39.98 with a p-value below 0.001. In short, both variables are influential, and job burnout is the most important factor causing Generation Z employees to consider leaving their jobs.